Role of ICT in Logistics Industry -An Employee Perspective - S Subhashini; S Preetha (International Journal of Supply Chain Management, 2018)
Abstract: ICT infrastructure in logistics sector has substituted the manual process by electronic exchange that has optimised the flow of information and documents between the service provider and the customer. Over the last few years, there has been a quick progress in the adoption of ICT in logistics sector. The communication tools like social networking, VoIP, Internet Telephony and email have been playing a leading role in securing a business as well as in providing service in an efficient manner. Moreover, the intelligent transportation systems also play a vital role in planning the route and enabling faster transfer of goods from one place to another. The increasing rivalry competition is one of the major force driving ICT usage. This study focuses on the influence of internet- based communication tools on increasing the efficiency of the employee and operation as well. This would enable us to understand the deployment of ICT on firms and on the logistics industry as well.